CLEAN AND HEALTHY LIVING BEHAVIOUR AND INFECTIOUS DISEASES (COVID-19) DIFFRERENCES BETWEEN DORMITORY AND HOME DURING THE COVID-19 PANDEMIC: - - Majida, Lia Awwalia; Irene Kartasurya, Martha; Achadi Nugraheni, Sri; Margawati, Ani; Noer, Etika (The Indonesian Journal of Public Health, 2024)
Introduction: Based on the results of the 2018 Basic Health Research, it was found that only 39.1% of households implemented clean and healthy living behavior (CHLB). During the COVID-19 pandemic, students living in dormitory and at home continue their studies at the Modern Islamic Boarding School. The differences in living conditions have an impact on Clean and Healthy Living Behavior (CHLB) and infectious diseases (COVID-19). Aims:  this research is to compare CHLB and infectious diseases (COVID-19) between students living at dormitory and home. Methods: A cross-sectional design study was conducted in January-February 2023 at Madrasah Aliah Mranggen, Demak, involving 232 students aged 16-18 years. The sample size is calculated using a formula to test the difference in means between two unpaired population groups with numerical data.  Subjects were selected through systematic random sampling based on inclusion and exclusion criteria. Data were collected using a household CHLB questionnaire. The data were analyzed using Mann Whitney and Chi Square Test. Results: showed no differences in age, CHLB, and infectious diseases among students living at dormitory and home. There were differences in handwashing with soap and water after using the toilet (p=0.041) and handling money (p=0.014), as well as the absence of smoking by dormitory mates/family members inside the Home/dormitory (p=0.001) between the two groups. Conclusion: There were no differences in CHLB and infectious diseases (COVID-19) between students living in dormitories and at home during the COVID-19pandemic.